Improving empiric antibiotic prescribing in pediatric bloodstream infections: a potential application of weighted-incidence syndromic combination antibiograms (WISCA). Issue 3 (4th March 2022) - Cook, Aislinn; Sharland, Mike; Yau, Yasmine; Group*, PediBSI; Bielicki, Julia
ABSTRACT: Background: Increasing antibiotic resistance to WHO-recommended first- and second-line treatments of pediatric sepsis requires adaptation of prescribing guidelines. We discuss the potential and limitations of a weighted-incidence syndromic combination antibiogram (WISCA) as a practical tool for incorporating local microbiology data when assessing empiric coverage of commonly used antibiotics. Research design and methods: A brief questionnaire of 18 clinically significant isolates from pediatric blood cultures (Jan-Dec 2018) was sent to a global network of pediatric hospitals in July 2019. Weighted coverage estimates of non-antipseudomonal third-generation cephalosporins (3GC) and meropenem were estimated using Monte–Carlo simulation for each site reporting >100 isolates. Results: 52 hospitals in 23 countries in 5 WHO regions responded to the questionnaire; 13 sites met the sample size requirement. The most common isolates were S. aureus, Klebsiella spp ., E. coli and Enterococcus spp. Coverage of 3GC ranged from 39% [95%CrI: 34–43%] to 73% (two sites: [95%CrI: 65–80%]; [95%CrI: 68–86%]) and meropenem coverage ranged from 54% [95%CrI: 47–60%] to 88% [95%CrI:84–91%]. Conclusions: A WISCA is a data-driven, clinically intuitive tool that can be used to compare empiric antibiotic regimens for pediatric sepsis using existing large datasets. The estimates can be further refined using more complex meta-analytical methods and patient characteristics.